FRI0261 Skin cancer in a cohort of systemic lupus erythematosus. (15th June 2017) - Taraborelli, M; Genitori, C; Cavazzana, I; Fredi, M; Tincani, A; Pinton, P Calzavara; Franceschini, F
Abstract : Background: Conflicting results about the prevalence of skin cancer in Systemic Lupus Erythematosus (SLE) have been reported in the literature [1, 2]. Objectives: The aim of this study was to retrospectively evaluate the prevalence of malignancies, with a particular focus on skin cancers, in a cohort of SLE patients followed in a single Center. Methods: All the SLE patients classified according to the ACR and SLICC criteria, attending the Rheumatology and Clinical Immunology Unit of Spedali Civili, Brescia, were retrospectively evaluated. Clinical and laboratory data were obtained from clinical charts. Diagnoses of skin cancers (melanoma and non-melanoma: basalioma, squamous cell carcinoma) and other malignancies were recorded together with the time elapsed from diagnosis of SLE. Univariate analysis was performed to compare characteristics of patients with (K+) and without (K-) cancer. We also compared the prevalence of cancer in our population to that reported in the italian general population (from the Italian National Institute of Statistics, ISTAT, report 2014). Results: In a cohort of 511 SLE patients (92% females, 95% caucasian) regularly followed from 1972 to 2016 (mean age at diagnosis 31 years±13 and median follow-up 12 years, range 1–40) we detected 51 cases (9, 9%) with a history of malignancy: melanoma was reported in 3 (0.5%), non melanoma skin cancer (NMSC) in 11 (2%) and other malignancies in 38 cases (7.4%). Table I reports the comparison between patients with and without cancer. Patients with cancer, as well as cases with NMSC and non cutaneous malignancies, showed a higher age at disease onset (p<0.0001; p=0.002 and p<0.0001 respectively) and higher SLE damage (p<0.0001; p=0.019 and p<0.0001 respectively) compared with patients without malignancies. Patients with melanoma showed the same age at SLE onset, but a higher prevalence of discoid lupus (p<0.0001) and oral ulcer history (p=0.02). No difference in serological SLE features or in disease activity were detected between groups. The prevalence of melanoma in our cohort (0.5%) was only slightly higher than the one reported in the northern Italian general population (0.2%), while the prevalence of NMSC (2%) resulted to be significantly higher than that reported in the same population (prevalence of spinocellular and basocellular cancer 0.1% and 0.5% respectively). Conclusions: Non-melanoma was the most common skin cancer observed in our SLE cohort. Its prevalence appeared to be higher than that reported in the general poopulation. SLE patients with melanoma showed a higher frequency of cutaneous lupus history compared with other SLE patients. References: Cao L et al PLoS One 2015;10:1–21. Goobie GC et al. Current Opinion Rheumatology 2015;27:454–60. Disclosure of Interest: None declared